From concept to form : in landscape design - Reid, Grant W. 4 0 16; 5 (New York : J. Wiley, 1993)
Presents a text on landscape design, with focus on translating concepts into specific organizations of space, and examines tradtional and non-traditional conceptual and philosophical foundations for landscaping.
Includes bibliographical references (p. 160) and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Landscape design; 20; 2